Analysis of Sediment Transport in the Galang-Galang River, Paku Village, Polewali Mandar Regency - Seri Tandira'pak; Erni Rante Bungin; Ika Apriyani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The Galang-Galang River or also known as the Binanga Karaeng River is a border river between the Polewali Mandar Regency (Polman) which was formerly known as Polmas before separating from South Sulawesi Province. During the rainy season, the water in this river often overflows and can even pose a danger to plantation and rice field farmers around the two border areas. Some of the rainwater that falls on the surface erodes the soil so that it is carried by the flow of water into the river downstream to make the sediment deposits increase. Sediment formed in the flow of the Galang - Galang river will cause a lack of river capacity during the dry season and in the rainy season, it will cause flooding. In this study, direct measurements and sampling of bottom sediment and floating sediment were carried out at three river points. The purpose of the study was to analyze deductions of basic sedimentary transports and sediments floating in the galange-Galang river. The study conducted direct measurements as well as retrieval of basic sedimentary samples and sediment rising at three points of the river. Basic sedimentary transport was calculated using the van rjin method, and for levitating sediments, it was calculated by a momentary method. From the results of the analysis, the bottom sediment transport discharge in the upstream is 4x10-4 tons/day, in the middle, it is 0.0891 tons/day, and in the downstream, it is 1x10-4 tons/day. Meanwhile, the floating sediment transport discharge is 0.208 tons/day upstream, 0.278 tons/day in the middle, and 0.121 tons/day downstream, where floating sediment transport is measured at a very small discharge so that the results are obtained are also small.